Watermelon waste as a growth media substitute for bacterial cellulose production - Muhammad Irhamni Haziqi, Nasharudin; Nazira, Mahmud; Mohd Hairul, Ab. Rahim (AIP Publishing, 2024)
Local fruits in Malaysia include tropical fruits that are rich in sugars. This includes watermelon which is grown largely on the east coast of Malaysia. However, due to reasons such as unpredictable weather changes, as well as the poor practice of harvesting and storage, a large portion of this fruit ends up rotten and dumped. The use of this fruit waste as a growth medium for bacterial cellulose production is seen as an excellent way to utilize it, in addition to encouraging the production of low-cost bacterial cellulose. Watermelon waste contains approximately 7 % sugars, a trace amount of protein and lipid, and the rest is moisture content. The treated watermelon waste from selected parameters was used in the fermentation of bacterial cellulose using Gluconacetobacter xylinus in an inoculum concentration of 8 and 10 %. The produced bacterial cellulose was quantified, analysed and compared to those using synthetic media. The moisture content, total solid, volatile solid, and fixed solid of watermelon were investigated which its recorded 97.45 %, 2.55 %, 2.18 %, and 0.76 % respectively. The carbohydrate content for treated watermelon was analysed by using phenol-sulphuric acid method, which the highest carbohydrate present was at 100 ℃ with watermelon waste to water ratio of 1:2, and 90 minutes incubation time. The BC pellicle’s produced was determined based on its BC yield, thickness, carbohydrate concentration before and after 16 days fermentation, and FTIR-ATR. The highest BC yield recorded was 1.0 cm (5.8090 mg/mL), which was cultured in treated watermelon waste only at 10 % inoculum density.